Coffee waste-derived porous carbon for hydrogen and oxygen evolution reaction - Keshab Pandey; Hae Kyung Jeong (Chemical Physics Impact, 2023)
Porous carbon was synthesized from coffee waste for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). The coffee waste was carbonized at 600 °C for 2 hrs and activated at 500, 600, and 700 °C, respectively. The activated coffee waste at 600 °C exhibits lower overpotential of -210 mV at -10 mA cm−2 and 230 mV at 10 mA cm−2 with lower Tafel slopes of 120 mV dec−1 and 140 mV dec−1 for HER and OER, respectively, compared to the samples at different activated temperature. The better HER and OER performances are associated to high electroactive surface area (3.9 × 10−5 cm2) and low charge transfer resistance (39 Ω) of the 600 °C activated sample, which also shows interconnected porous structure, in comparison with the other samples. The coffee waste after the carbonization and activation could be applied for HER and OER electrocatalyst.